Fast cycling of intermittent hypoxia in a physiomimetic 3D environment: A novel tool for the study of the parenchymal effects of sleep apnea - Jurado, Alicia; Ulldemolins, Anna; Lluís, Helena; Gasull, Xavier; Gavara, Núria; Sunyer, Raimon; Otero, Jorge; Gozal, David; Almendros, Isaac; Farré, Ramon (Frontiers in Pharmacology, 2023)
Background. Patients with obstructive sleep apnea (OSA) experience recurrent hypoxemic events with a frequency sometimes exceeding 60 events/h. These episodic events induce downstream transient hypoxia in the parenchymal tissue of all organs, thereby eliciting the pathological consequences of OSA. Whereas experimental models currently apply intermittent hypoxia to cells conventionally cultured in 2D plates, there is no well-characterized setting that will subject cells to well-controlled intermittent hypoxia in a 3D environment and enable the study of the effects of OSA on the cells of interest while preserving the underlying tissue environment. Aim. To design and characterize an experimental setup that exposes cells to high-frequency intermittent hypoxia mimicking OSA in 3D (hydrogels or tissue slices). Methods. Hydrogels made from lung extracellular matrix (L-ECM) or brain tissue slices (300-800-μm thickness) were placed on a well whose bottom consisted of a permeable silicon membrane. The chamber beneath the membrane was subjected to a square wave of hypoxic/normoxic air. The oxygen concentration at different depths within the hydrogel/tissue slice was measured with an oxygen microsensor. Results. 3D-seeded cells could be subjected to well-controlled and realistic intermittent hypoxia patterns mimicking 60 apneas/h when cultured in L-ECM hydrogels ≈500 μm-thick or ex-vivo in brain slices 300-500 μm-thick. Conclusions. This novel approach will facilitate the investigation of the effects of intermittent hypoxia simulating OSA in 3D-residing cells within the parenchyma of different tissues/organs.